ARCHITECTURAL DESIGNS INSPIRED BY NATURE AND MATHEMATICAL MODELS - Taş, Aslı; Avinç, Güneş Mutlu (St. Petersburg State University of Architecture and Civil Engineering, 2025)
This paper explores how nature-inspired mathematical models and principles are applied in architectural design and how these approaches contribute to innovative and sustainable solutions. Architectural structures incorporating nature-inspired and mathematical models have been widely studied in the literature. However, research examining the relationship between nature and mathematics specifically within the field of architecture remains limited. Addressing this gap, the study investigates the interplay between mathematics and nature in architectural design. Its contribution lies in providing a holistic examination of mathematical models in architecture. Within the scope of the study, five examples demonstrating different mathematical theorems were analyzed. Methods: The structures were evaluated using qualitative content analysis, while the mathematical models were identified through visual content analysis. The findings are summarized in a table. Conclusion: Architecture is profoundly shaped by the relationship between nature and mathematics. Analyzing the mathematics inherent in nature and applying these principles in design serves as a guide for creating aesthetically pleasing, sustainable, and innovative buildings. © (2025), (St. Petersburg State University of Architecture and Civil Engineering). All rights reserved.
АРХИТЕКТУРНЫЕ ПРОЕКТЫ, ВДОХНОВЛЕННЫЕ ПРИРОДОЙ И МАТЕМАТИЧЕСКИМИ МОДЕЛЯМИ
Keywords: Fractal Geometry; Golden Ratio; Mathematical Model; Mathematics In Architecture; Nature-Inspired Architecture; архитектура; вдохновленная природой; золотое сечение; математика в архитектуре; математическая модель; фрактальная геометрия